Reformulation of Chemical Castration Sanctions for Perpetrators of Sexual Crimes in Review from the Relative Theory of Punishment - Fanita Aditia; Emilda Firdaus; Davit Rahmadan (Melayunesia Law, 2024)
This research aims to see whether or not chemical castration sanctions are applied to sex offenders when viewed from the Relative Theory of Punishment and is associated with several examples of decisions. From the research results. The application of chemical castration sanctions against sex offenders has not been implemented effectively in law enforcement in Indonesia because there is still a discrepancy between the provisions of additional punishment determined by the legislator with the facts or circumstances that occur. The Relative theory of punishment views the provision of punishment not as retaliation for the wrongdoing committed by the perpetrator, the justification of punishment lies in its purpose, namely to reduce the frequency of crime. Therefore, it is necessary to reformulate the sanction of chemical castration from various aspects, including socio-philosophical, socio-political, and socio-cultural aspects. The need for a legal breakthrough to provide therapeutic/treatment effects to perpetrators of sexual crimes through psychiatric rehabilitation efforts. Because basically, punishment is no longer solely as retaliation, but to re-educate the person who committed the criminal act to become a useful member of society.